JOB RISK ASSESSMENT PEKERJAAN BONGKAR MUAT DI UD XYZ BALIKPAPAN - Zainul, L.M. Zainul (Program Studi Kesehatan dan Keselamatan Kerja, 2018)
UD XYZ is a food & beverages and health product distribution company, where the work carried out has the risk of workplace accidents as well as other transportation distribution jobs. Moreover, in the lifting process, starting from the supply of material to the delivery process, it requires lifting work. In various jobs, sometimes it takes to move heavy objects from one place to another or to a higher place, which usually requires a tool to perform the removal process, from the tools such as chain block, pulley or using more complex tools that are a crane. The study aims to determine the risk of goods loading and unloading work. The study used a qualitative method with a crossectional approach. Risk identification and analysis using the Job Risk Assessment (JRA) method.A risk event identified by 22 kinds. Risks that have a very high-risk rating (very high) are unspoiled goods and workers crashing vehicles. Category substantially has 3 items that hit workers, fire and workers exposed to fuel vapours. The priority category in the risk assessment is 9 items, while the accepted risk (acceptable) is 10 items.